1976
DOI: 10.1111/j.1651-2227.1976.tb04952.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Studies in Phenylketonuria

Abstract: Abstract. Significantly reduced immunoglobulins were found in 22 patients with phenylketonuria. Tests of cellular immune function which included delayed skin hypersensitivity, T rosettes and PHA transformation were normal. Escherichia coli antibodies and the booster response to tetanus toxoid were also normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…Our study confirms that immunoglobulin levels (primarily Ig and IgG levels) are altered in children with PKU (Passwell et al 1976;Giovannini et al 1988). Imbalances in immunoglobulin classes IgG and IgE are similar to imbalances found in some cases of common variable hypogammaglobulinaemia (Zwetchenbaum 1990) and have been described in atopic eczema (Reinhold et al 1988).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study confirms that immunoglobulin levels (primarily Ig and IgG levels) are altered in children with PKU (Passwell et al 1976;Giovannini et al 1988). Imbalances in immunoglobulin classes IgG and IgE are similar to imbalances found in some cases of common variable hypogammaglobulinaemia (Zwetchenbaum 1990) and have been described in atopic eczema (Reinhold et al 1988).…”
Section: Discussionsupporting
confidence: 88%
“…Little is known about the immunological features of children with PKU. Although immunological indices of these children were previously considered to be normal (Abba et al 1966), low IgG, IgM and Iga levels were subsequently described in 22 children aged 7 months to 21 years who had not been placed on diet therapy (Passwell et al 1976). These authors suggested a causal relationship between low levels of *Correspondence MS received 18.5.94 Accepted 4.7.94 immunoglobulins and reduced availability of tyrosine, an amino acid highly represented in antibodies.…”
mentioning
confidence: 99%
“…El unico trabajo publicado muestra que no existe altera- cifras corresponden al promedio geome'trico, entre cion de la rcspuesta cutanea de hipersensibilidad retardada, del niimero de linfocitos T y de la capacidad proliferativa de linfocitos frente a PHA 17 . Sin embargo, los invcstigadores no realizaron una curva dosis-respuesta e incluso no senalan la concentracion dc mitogeno ulilizado 17 . En nuestro estudio realizamos una curva dosis-respuesta frente a PHA en cada pacicnte, antes y despue"s de la suplementacion con /inc.…”
Section: Comentariounclassified